Determination of reference values for third trimester amniotic fluid index: a retrospective analysis of a large cohort of pregnancies with comparison to previous nomograms. (2nd January 2022) - Gabbay-Benziv, Rinat; Maor-Sagie, Estie; Shrim, Alon; Hallak, Mordechai
Abstract: Purpose: To establish a new set of reference values for third-trimester amniotic fluid index (AFI) and compare them to other previously published normograms. Methods: A retrospective cross-sectional cohort analysis of all singleton sonographic evaluations >22 gestational weeks in one university affiliated medical center between 2013 and 2017. Pregnancies complicated by rupture of membranes, major anomalies/chromosomal abnormalities were excluded. One evaluation per patient per pregnancy was randomly selected. Reference values were constructed using a best-fit regression model for estimation of mean and standard deviation at each gestational age after normalization of variables and compared with previously published norms. Results: A total of 7037 ultrasound evaluations entered the analysis. Correlation between AFI and gestational age was best represented by a first-degree polynomial equation. AFI decreased gradually from 16.4 at 22 weeks to 13.3 at 40 weeks (cm, median). The standard deviation increased with gestational age with AFI ranging from 12.9–20.2 at 22 weeks and 4.7–26.2 at 40 weeks (cm, 2.5–97.5 percentile). Compared to other curves, our reference values demonstrated a higher median AFI throughout all gestation. Conclusions: Reference values for the third trimester AFI were established. Curves should be correlated with perinatal outcome prior to wide clinical implementation.